Economic barriers, evidentiary gaps, and ethical conundrums: a qualitative study of physicians' challenges recommending HPV vaccination to older gay, bisexual, and other men who have sex with men - Daniel Grace; Mark Gaspar; Ron Rosenes; Ramandip Grewal; Ann N. Burchell; Troy Grennan; Irving E. Salit (BMC, 2019)
Abstract Background The human papillomavirus (HPV) is the most common sexually transmitted infection (STI) worldwide. Gay, bisexual, and other men who have sex with men (GBM), and GBM living with HIV in particular, are disproportionately impacted by HPV-associated cancers. The HPV vaccine, given early enough in life, may markedly reduce the likelihood of such cancers. In Canada, most provincial insurance programs only cover HPV vaccination for GBM up to the age of 26. Our objective was to understand physicians' everyday experiences and challenges in recommending HPV vaccination to older GBM patients. Methods As part of the HPV Screening and Vaccine Evaluation (HPV-SAVE) Study, we conducted semi-structured interviews with 25 HIV-positive GBM patients who had received anal cancer screening and 15 service providers, including 13 physicians, who had arranged for anal cancer screening in the Canadian provinces of Ontario and British Columbia. In this analysis, we draw upon the 13 physician interviews, which were coded following Grounded Theory. Results Physicians strongly supported the HPV vaccine for all GBM and considered it to be important for the management of HIV-related care. However, the overall support for HPV vaccination among physicians did not translate into consistent recommendation practices. There were two overarching factors that limited the strength/frequency of physicians' vaccine recommendation practices. First, cost/insurance coverage for some older patients impacted if and how the HPV vaccine was discussed. Second, physicians had diverse perspectives on both the prevention and therapeutic benefits of vaccinating older GBM and the reality that national guidelines are incongruent with publicly funded vaccine programs for vaccinating patients over 26 years old. These two interrelated factors have co-produced an apparent economic-evidentiary conundrum for many physicians regarding how and for whom to offer HPV vaccination. Conclusion Economic barriers coupled with evidentiary and guideline gaps have created clinical practice challenges for physicians and has resulted in different messages being communicated to some older GBM patients about how important HPV vaccination is for their health.